2001
DOI: 10.1007/s00268-001-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic Cerebrospinal Fluid Leakage

Abstract: Posttraumatic cerebrospinal fluid (CSF) leakage frequently complicates skull base fractures. While most CSF leaks will cease without treatment, patients with persistent CSF leaks may be at increased risk for meningitis, and many will require surgical intervention. We reviewed the medical records of 51 patients treated between 1984 and 1998, with CSF leaks that persisted for 24 hours or longer after head trauma. Twenty-eight patients (53%) had spontaneous resolution of the leakage at an average of 5 days. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
139
1
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 17 publications
(14 reference statements)
4
139
1
10
Order By: Relevance
“…3) The frequency of different types of CSF leakage, such as rhinorrhea or otorrhea, was not defined in previous reports. A total of 27 cases of CSF leakage occurred among 1036 cases of closed head injury.…”
Section: Discussionmentioning
confidence: 99%
“…3) The frequency of different types of CSF leakage, such as rhinorrhea or otorrhea, was not defined in previous reports. A total of 27 cases of CSF leakage occurred among 1036 cases of closed head injury.…”
Section: Discussionmentioning
confidence: 99%
“…CSF leakage has been reported to stop 4.1 days (mean value) after trauma and 5.3 days after lumbar drainage, and ratio of spontaneous cessation has been reported to be 61%. [5,8] Surgical treatment should be considered in cases with leak that persists for more than one week. [12,13] However, there are some exceptions to this principal management strategy such as high risk elderly patients, patients with diabetes mellitus and immunosuppressed condition, associated intracranial pathologies or profuse leaks.…”
Section: Discussionmentioning
confidence: 99%
“…[8,12,14] Similarly, patients with severe head trauma or low GCS should be managed with radical surgical measures since the risk of infectious complications or neurological deterioration is quite high. [5,8] Surgical intervention should also be considered for cases with subdural or epidural hematomas, tension pneumocephalus, depression fractures including comminuted skull base fractures or patients with severe contusion and edema. These lesions require decompressive measures, all of which limit the use of lumbar drainage or temporary lumbar punctures for CSF fistulae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Friedman et al conducted a review of 51 head injury patients from 1984 to 1988 and showed that only 10% of patients developed meningitis with antibiotic prophylaxis, as compared to 21% in the group without antibiotics. 29 The study was only retrospective and the level of evidence was not strong. However, with respect to the severity of the complications, antibiotics are usually given.…”
Section: U L T U Re S Y I E L D E D M a I N L Y C O A G U L A S E N Ementioning
confidence: 99%